Deskripsi Self-Efficacy Berpikir Kritis Matematis Siswa pada Pembelajaran Socrates Saintifik - Khusnul Khotimah; Tina Yunarti (Limacon: Journal of Mathematics Education, 2019)
This qualitative research was aimed to describe student's mathematical critical thinking self-efficacy on Socrates' scientific learning. The subjects of this research were the students of the VII-A class of SMPN 1 Natar academic year 2017/2018. This research data was qualitative data about mathematical critical thinking of students obtained through scale sheets of self-efficacy, observation sheets, interviews, and journals. Data analysis was done through three stages, namely data reduction, data presentation, and conclusion verification. Based on the result of the research, it could be concluded that in critical mathematical conversation there was a student's mathematical critical thinking self-efficacy which predominantly emerge during mathematics learning by using the Socrates Scientific method. They were feeling interested, optimistic and confident in the dimensions of magnitude/level, also increasing the efforts in the dimensions of strength, and were guided by previous learning experience in the dimension of generality.